The perception of third year students of Iloilo National High School on teaching performance - Alfuente, Clarette Brenda; Cuñada, GV Eutiquio; Dequito, Dax; Gargaritana, Ryan Jay; Pacleb, Pamela Ann
This study was conducted last November 2001, on the topic "The perception of third year students of Iloilo National High School on teaching performance." The major finding in this study is that, the commonly used, most preferred, and the most effective teaching method in Iloilo National High School is Lecture-Discussion. Furthermore, the respondents' gender and place of residence does not affect their perception on teaching performance.